Patterns of conflict, paths to peace - Fisk, Larry; Schellenberg, John. ([S.l.] : Broadview Press, 2000)
This book aims to build bridges to peace by spanning the fields of conflict resolution and traditional peace studies, and by facing the contending perspectives of academics and practitioners. It serves not only as a transdisciplinary introduction to the study of peace and conflict but as an intelligent and sensitive challenge to common understandings. Positive peace, conflict transformation, contemporary peacekeeping, non-violent action, peace education and the new peace movements are laid out for consideration and basic concepts and directions are covered. But more important is the critical evaluation of patterns and the plotting of alternative paths. As UNESCO promotes an International Year of the Culture of Peace (2000) and the United Nations sponsors a decade of peace culture (2000 to 2010), the essays in Patterns of Conflict, Paths to Peace represent an invaluable primer for anyone concerned to participate in such a culture.
Keywords: Peace